2019
DOI: 10.1021/acs.chemrestox.9b00154
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation Theory Machine Learning Modeling of Immunotoxicity for Drugs Targeting Inflammatory Cytokines and Study of the Antimicrobial G1 Using Cytometric Bead Arrays

Abstract: ChEMBL biological activities prediction for 1–5-bromofur-2-il-2-bromo-2-nitroethene (G1) is a difficult task for cytokine immunotoxicity. The current study presents experimental results for G1 interaction with mouse Th1/Th2 and pro-inflammatory cytokines using a cytometry bead array (CBA). In the in vitro test of CBA, the results show no significant differences between the mean values of the Th1/Th2 cytokines for the samples treated with G1 with respect to the negative control, but there are moderate differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…To consider both the structure of any case/chemical and the experimental condition, cj, under which that case/chemical was tested, we applied a two-step approach, known as Box–Jenkins, which is the key aspect accounting for the great success of the PTML models [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 57 , 58 , 59 , 60 , 61 , 62 ]: …”
Section: Methodsmentioning
confidence: 99%
“…To consider both the structure of any case/chemical and the experimental condition, cj, under which that case/chemical was tested, we applied a two-step approach, known as Box–Jenkins, which is the key aspect accounting for the great success of the PTML models [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 57 , 58 , 59 , 60 , 61 , 62 ]: …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we calculated a series of topological indices that fused chemical and biological information. To do so, we employed an adaptation of the Box-Jenkins approach, which is the key of the PTML modeling philosophy and for which great successful applications in different research areas have been reported in the scientific literature [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 55 , 56 , 57 ]. In the first step of this approach, we used the following mathematical formula: …”
Section: Methodsmentioning
confidence: 99%
“…Particularly, as depicted in Table 1 , the purpose here was to build an mtc-QSAR-MLP model to predict the inhibitory activity of a molecule under eight different experimental conditions. As mentioned in the previous section, such a capability of simultaneously predicting complex biological endpoints under dissimilar experimental conditions is an intrinsic characteristic of any PTML model [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 55 , 56 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the significance of computational drug discovery, over the last 10 years, several research groups have emphasized the development and application of the methodology known as Perturbation Theory and Machine Learning (PTML) through which it has been possible to overcome all the drawbacks of the in silico approaches mentioned above. Thus, PTML models have been able to integrate chemical and biological data at different levels of complexity in scientific areas as diverse as antimicrobial research, oncology, neurosciences, immunology, and peptide/protein science. In doing so, PTML models have been able to predict multiple activities, toxicities, and/or pharmacokinetic end points, while considering dissimilar biological targets (e.g., proteins, microorganisms, cells, rodents, etc.) and many assay protocols.…”
Section: Introductionmentioning
confidence: 99%